Diversity and Composition of Macroalgae in the Rambang Delta, East Lombok - Ghazali, Mursal; Artiningrum, Novita Tri; Setyaningrum, Tri Wahyu; Nurhayati, Nurhayati; Murdiah, Murdiah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Delta ecosystems represent dynamic coastal transition zones that play a crucial role in maintaining ecological balance and supporting biological productivity. The Rambang Delta in East Lombok, Indonesia, is influenced by tidal mixing and freshwater discharge, creating heterogeneous environmental conditions that support diverse benthic macroalgae communities. This study aimed to analyze the composition, diversity, and spatial distribution of macroalgae and evaluate the influence of environmental parameters on community structure across three sampling stations exposed to aquaculture activities. Macroalgae samples were collected using purposive sampling within 1×1 m plots, identified morphologically, and analyzed using species importance value index (INP), Shannon–Wiener diversity (H′), evenness (E), and Simpson dominance index (D). Ten water quality parameters were measured in situ and exitu to assess ecological conditions. The results of the study indicate that the environmental parameters of the research location are partly within the environmental quality standards, such as temperature, salinity, pH, and current. While turbidity, PO4-P, NH3-N, and DO are outside the environmental quality standards. The number of species found was 56, consisting of 25 species of chlorophyta macroalgae, 19 species of Rhodophyta, and 12 species of Phaeophyta. Station 1 has an H′ value of 1.9, while Station 2 and Station 3 have values of 2.6 and 2.7, respectively. Meanwhile, the uniformity index (E) value at Station 1 is 0.63, 0.66 at Station 2, and 0.74 at Station 3. In contrast, the dominance index (D) at Station 1 is 0.22, and Stations 2 and 3 have a dominance index value of 0.12.